Strategi Guru PAI dalam Menginternalisasikan Nilai Spiritual di Kalangan Siswa Era Digital (Studi Kasus di SMK PGRI 1 Pasuruan) - Akhmad Zubaidillah; M. Ma’ruf; Jakaria Umro (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
Digital technology greatly influences students’ moral and spiritual development. The rapid flow of information often decreases students’ spiritual awareness. This condition requires Islamic Education (PAI) teachers to apply effective strategies in instilling spiritual values. This study aims to describe the strategies of PAI teachers in internalizing spiritual values in the digital era. The research used a qualitative case study approach, with data collected through observation, interviews, and documentation. The results show that PAI teachers apply direct guidance, motivation, and student participation in religious activities while serving as role models through discipline and piety. Supporting factors include school support, worship facilities, and teacher collaboration, while obstacles include low student interest, social media influence, limited time, and lack of parental involvement.